2013
DOI: 10.3168/jds.2012-6045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an exogenous amylase on performance and total-tract digestibility in lactating dairy cows fed a high-byproduct diet

Abstract: The objective of this experiment was to determine the performance and digestibility response of lactating dairy cows fed a reduced-starch diet containing a commercial amylase product. Treatments consisted of a normal-starch total mixed ration (NS-), a reduced-starch total mixed ration (RS-), and a reduced-starch total mixed ration with exogenous amylase (RS+) added to the concentrate. Treatments were assigned according to a replicated 3 × 3 Latin square design with 28-d periods. Twenty-three cows completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
1
20
1
1
Order By: Relevance
“…The increase in V 1 , V 2, C 1 and C 2 with amylase inclusion indicates higher digestibility of both non-fibrous and fibrous fractions of silage, which strengthens the occurrence of cross-feeding interaction among the micro-organisms. Similarly, amylase supplementation increased the total NDF digestibility when evaluated in vivo (Gencoglu et al, 2010;Mccarthy et al, 2013). Contrary to our study, others did not found effect of addition of the exogenous amylase on NDF digestibility for dairy cows (Andreazzi et al, 2018;Zilio et al, 2019).…”
Section: Fermentation Kinetics and In Vitro Dry Matter Digestibilitycontrasting
confidence: 96%
See 3 more Smart Citations
“…The increase in V 1 , V 2, C 1 and C 2 with amylase inclusion indicates higher digestibility of both non-fibrous and fibrous fractions of silage, which strengthens the occurrence of cross-feeding interaction among the micro-organisms. Similarly, amylase supplementation increased the total NDF digestibility when evaluated in vivo (Gencoglu et al, 2010;Mccarthy et al, 2013). Contrary to our study, others did not found effect of addition of the exogenous amylase on NDF digestibility for dairy cows (Andreazzi et al, 2018;Zilio et al, 2019).…”
Section: Fermentation Kinetics and In Vitro Dry Matter Digestibilitycontrasting
confidence: 96%
“…(2016) observed that amylase decreased lag time and increased rate and amount of gas production. This effect of amylase is due to the greater hydrolysis of starch (Nozière et al, 2014) providing substrates for the multiplication of other microbial species, mainly fibrolytic micro-organisms (Mccarthy, Engstrom, Azem, & Gressley, 2013), a process defined as cross-feeding among rumen micro-organisms (Russell, 1985) that can improve fibre digestibility by increase in fibre digestion rate as shown in our study.…”
Section: Fermentation Kinetics and In Vitro Dry Matter Digestibilitymentioning
confidence: 64%
See 2 more Smart Citations
“…Early research attempts on supplementation ruminant diet with exogenous enzymes has a considerable long history which took place in 1960's, mainly considering the amylolytic (McCarthy et al, 2013) and proteolytic (Vera et al, 2012) enzymes. But the inconsistency of the obtained results, less knowledge on mode of action of enzymes and the high production cost of enzymes hindered the further development of this field.…”
Section: Introductionmentioning
confidence: 99%